Freehand Stereotactic Image-Guidance Tailored to Neurotologic Surgery - Schneider, Daniel; Anschuetz, Lukas; Mueller, Fabian; Hermann, Jan; O'Toole Bom Braga, Gabriela; Wagner, Franca; Weder, Stefan; Mantokoudis, Georgios; Weber, Stefan; Caversaccio, Marco (Frontiers in Surgery, 2021)
Hypothesis: The use of freehand stereotactic image-guidance with a target registration error (TRE) of µTRE+3σTRE<0.5 mm for navigating surgical instruments during neurotologic surgery is safe and useful. Background: Neurotologic microsurgery requires work at the limits of human visual and tactile capabilities. Anatomy localization comes at the expense of invasiveness caused by exposing structures and using them as orientation landmarks. In the absence of more-precise and less-invasive anatomy localization alternatives, surgery poses considerable risks of iatrogenic injury and sub-optimal treatment. There exists an unmet clinical need for an accurate, precise, and minimally-invasive means for anatomy localization and instrument navigation during neurotologic surgery. Freehand stereotactic image-guidance constitutes a solution to this. While the technology is routinely used in medical fields such as neurosurgery and rhinology, to date, it is not used for neurotologic surgery due to insufficient accuracy of clinically available systems. Materials and methods: A freehand stereotactic image-guidance system tailored to the needs of neurotologic surgery–most importantly sub-half-millimeter accuracy–was developed. Its TRE was assessed preclinically using a task-specific phantom. A pilot clinical trial targeting N=20 study participants was conducted (ClinicalTrials.gov ID: NCT03852329) to validate the accuracy and usefulness of the developed system. Clinically, objective assessment of the TRE is impossible because establishing a sufficiently accurate ground-truth is impossible. A method was used to validate accuracy and usefulness based on intersubjectivity assessment of surgeon ratings of corresponding image-pairs from the microscope/endoscope and the image-guidance system. Results: During the preclinical accuracy assessment the TRE was measured as 0.12±0.05 mm (max: 0.27 mm, µTRE+3σTRE=0.27 mm, N=310). During an endoscopic cholesteatoma removal, a microscopic facial nerve schwannoma removal, and a microscopic vestibular schwannoma removal, N=75 accuracy and usefulness ratings were collected from five surgeons each grading 15 image-pairs. On a scale from 1 (worst rating) to 5 (best rating), the median (interquartile range) accuracy and usefulness ratings were assessed as 5 (4 to 5) and 4 (4 to 5) respectively. Conclusion: Navigating surgery in the tympanomastoid compartment and potentially in the lateral skull base with sufficiently accurate freehand stereotactic image-guidance (µTRE+3σTRE<0.5 mm) is feasible, safe, and useful.